Firm and industry characteristics of exchange rate exposure and optimal hedging strategy: Evidence on China - YAN, Fen (Institutional Knowledge at Singapore Management University, 2010)
Understanding the effect of foreign exchange rate movements on the value of firm is a critical element for the purpose of risk management. In this thesis, firm and industry specific exposures to exchange rate movements in the Chinese market before and after the exchange rate regime reform in 2005 are examined. We observe that at the one-week return horizon, among all the firms listed in the China Exchange Market before the year 2001, less than 10% of the firms exhibit significant "residual exposure" to bilateral exchange rate movements against China’s major trading partners before the reform. In contrast, the proportion of firms with significant exposure increase to over 20% for some bilateral exchange rates after the reform. The "total exposure" is measured by using orthogonal market returns in place of market returns and a much higher percentage of firms exhibit significant "total exposure". We also observe that the number of firms with significant exposure increases with the return time horizon, regardless of whether it is residual exposure or total exposure. The phenomenon of asymmetric exposure is also examined; the results show that 4.5% of firms exhibit asymmetric exposure during appreciation and depreciation cycles with respect to all the major bilateral exchange rates and the percentage of firms with asymmetrical exposure also increase with the return horizon. As for the industry-specific exposure, about 90% of Chinese industries at the three-digit SIC level are significantly exposed to both bilateral and trade-weighted exchange rate movements. The predominantly positive exposure effect indicates that most industries behave like net exporters and benefit from the depreciation of RMB. Theoretical models are built to simulate how firms in export, import and import-competing industries make decisions to maximize their profits when foreign exchange rates fluctuate. We show that our models are consistent with the observed empirical relationship between the exchange rate exposure of the Chinese industries and the import elasticity against the U.S. dollar and the Japanese yen.